Potential pest transfer mediated by international ornamental plant trade - Patoka, Jiří (Sci Rep, 2016)
In recent years, the keeping of ornamental freshwater animals and plants in garden ponds has been growing in popularity. Water hyacinth (Eichhornia crassipes) is one of the preferred macrophytes seasonally imported mainly from South-eastern Asia throughout the world. This constitutes a secondary introduction inasmuch as the species is native to South America. Although many assemblages of aquatic invertebrates have been described as associated with this plant in the wild, there has been no research focused on their potential introduction via the international plant trade. We examined 216 specimens of water hyacinths imported for ornamental purposes from Indonesia into the Czech Republic. Numerous meio- and macroinvertebrates belonging to at least 39 species were captured. On the total number of individuals, the highest prevalence was of Tubulinea and Rotifera. Most of these were still alive and vital, including a caterpillar of the Indo–Australian invasive moth Spodoptera litura. Water hyacinths are usually placed into outdoor ponds immediately after import, which facilitates the release of non-target alien species. The present paper aims to draw attention to “hitchhikers” associated with the ornamental trade.